High serum dihydrotestosterone examined by ultrasensitive LC‐MS/MS as a predictor of benign prostatic hyperplasia or Gleason score 6 cancer in men with prostate‐specific antigen levels of 3–10 ng/mL. (3rd November 2016) - Miyoshi, Y.; Uemura, H.; Suzuki, K.; Shibata, Y.; Honma, S.; Harada, M.; Kubota, Y.
Summary: There has been no consensus on the role of serum androgen concentrations in prostate cancer detection in men with prostate‐specific antigen levels of 3–10 ng/mL. In this study, testosterone and dihydrotestosterone concentrations in blood were examined by a newly developed method using ultrasensitive liquid chromatography with two serially linked mass spectrometers (LC‐MS/MS). We investigated the correlation between serum androgen levels and Gleason scores at biopsy. We analyzed data of 157 men with a total prostate‐specific antigen range of 3–10 ng/mL who underwent initial systematic prostate needle biopsy for suspected prostate cancer between April 2000 and July 2003. Peripheral blood testosterone and dihydrotestosterone concentrations were determined by LC‐MS/MS. Blood levels of testosterone and dihydrotestosterone were compared with pathological findings by multivariate analyses. Median values of prostate‐specific antigen and prostate volume measured by ultrasound were 5.7 ng/mL and 31.4 cm 3, respectively. Benign prostatic hyperplasia was diagnosed in 97 patients (61.8%), and prostate cancer was diagnosed in 60 (38.2%) patients, including 31 (19.7%) patients with a Gleason score of 6 and 29 (18.5%) patients with a Gleason score of 7–10. Median values of testosterone and dihydrotestosterone in blood were 3798.7 and 371.7 pg/mL, respectively. There was a strong correlation between serum testosterone and dihydrotestosterone. In multivariate analysis, age, prostate volume, and serum dihydrotestosterone were significant predictors of benign prostatic hyperplasia or prostate cancer with a Gleason score of 6. The area under the receiver operating characteristics curve for age, prostate volume, and serum dihydrotestosterone were 0.67, 0.67, and 0.67, respectively . We confirmed that high dihydrotestosterone blood levels can predict benign prostatic hyperplasia or prostate cancer with a Gleason score of 6 in men with prostate‐specific antigen levels of 3–10 ng/mL.